Strengthening individual capacity in monitoring and evaluation of malaria control programmes to streamline M&E systems and enhance information use in malaria endemic countries - Garley, Ashley (Malar J, 2016)
BACKGROUND: Malaria control interventions in most endemic countries have intensified in recent years and so there is a need for a robust monitoring and evaluation (M&E) system to measure progress and achievements. Providing programme and M&E officers with the appropriate skills is a way to strengthen malaria’s M&E systems and enhance information use for programmes’ implementation. This paper describes a recent effort in capacity strengthening for malaria M&E in sub-Saharan Africa (SSA). METHODS: From 2010 to 2014, capacity-strengthening efforts consisted of organizing regional in-person workshops for M&E of malaria programmes for Anglophone and Francophone countries in SSA in collaboration with partners from Ghana and Burkina Faso. Open-sourced online courses were also available in English. A post-workshop assessment was conducted after 5 years to assess the effects of these regional workshops and identify gaps in capacity. RESULTS: The regional workshops trained 181 participants from 28 countries from 2010 to 2014. Trained participants were from ministries of health, national malaria control and elimination programmes, non-governmental organizations, and development partners. The average score (%) for participants’ knowledge tests increased from pretest to posttest for Anglophone workshops (2011: 59 vs. 76, 2012: 41 vs. 63, 2013: 51 vs. 73; 2014: 50 vs. 74). Similarly, Francophone workshop posttest scores increased, but were lower than Anglophone due to higher scores at pretest. (2011: 70 vs. 76, 2012: 74 vs. 79, 2013: 61 vs. 68; 2014: 64 vs. 75). Results of the post-workshop assessment revealed that participants retained practical M&E knowledge and skills for malaria programs, but there is a need for a module on malaria surveillance adapted to the pre-elimination context. CONCLUSION: The workshops were successful because of the curriculum content, facilitation quality, and the engagement of partner institutions with training expertise. Results from the post-workshop assessment will guide the curriculum’s development and restructuring for the next phase of workshops. Country-specific malaria M&E capacity needs assessments may also inform this process as countries reduce malaria burden.